Comparison of Rumen Fermentation Parameters and Microbiota of Yaks From Different Altitude Regions in Tibet, China - Han, Lulu; Xue, Wanchao; Cao, Hanwen; Chen, Xiaoying; Qi, Fasheng; Ma, Tao; Tu, Yan; Diao, Qiyu; Zhang, Chengfu; Cui, Kai (Frontiers in Microbiology, 2022)
Rumen microbiota are closely linked to feed utilization and environmental adaptability of ruminants. At present, little is known about the influence of different extreme environments on the rumen microbiota of yaks. In this study, 30 ruminal fluid samples from 30 healthy female yaks (average 280 kg of BW) in 5–8 years of life were collected from three regions in Tibet, China, and compared by gas chromatography and high-throughput sequencing. Results showed that propionic acid, butyric acid, and total volatile fatty acids were significantly (P < 0.05) higher, while microbial abundance and diversity were significantly (P < 0.05) lower, in the Nagqu (4,500 m altitude) compared to the Xigatse (4,800 m altitude) and Lhasa (3,800 m altitude) regions. Principal coordinate analysis revealed significant (P < 0.05) differences in rumen microbial composition of yaks from different regions. Specifically, Bacteroidetes and Firmicutes were identified by linear discriminant analysis effect size (LDA > 3) as being the signature phyla for Xigatse and Nagqu regions, respectively. Additionally, the relative abundance of Rikenellaceae_RC9_gut_group, Quinella, Prevotellaceae_UCG-003, Lachnospiraceae_NK3A20_group, Papillibacter, Ruminococcaceae_UCG-010, Prevotellaceae_NK3B31_group, and Ruminococcaceae_UCG-005 correlated with altitude and rumen fermentation parameters (P < 0.05). Finally, the predicted function of rumen microbiota was found to differ between regions (P < 0.05). In summary, our results reveal that regions located at different altitudes influence microbiota composition and fermentation function of yaks’ rumen. The present findings can provide mechanistic insights on yak adaptation to high altitudes and improve the feeding efficiency of these animals in extreme regions.